2018
DOI: 10.1038/s41598-018-23198-5
|View full text |Cite
|
Sign up to set email alerts
|

Species Level Description of the Human Ileal Bacterial Microbiota

Abstract: The small bowel is responsible for most of the body’s nutritional uptake and for the development of intestinal and systemic tolerance towards microbes. Nevertheless, the human small bowel microbiota has remained poorly characterized, mainly owing to sampling difficulties. Sample collection directly from the distal ileum was performed during radical cystectomy with urinary diversion. Material from the ileal mucosa were analysed using massive parallel sequencing of the 16S rRNA gene. Samples from 27 Caucasian pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 50 publications
8
59
0
Order By: Relevance
“…The epithelial channel of the chips was flushed daily with a short (2 min) fluid pulse at higher flow rate (50 l.min -1 ) to remove adherent and luminal bacteria, and 16S rRNA sequencing was carried out using samples from the effluent to assess bacterial diversity in each condition over 3 days of culture (n = 4 for each condition). 11 After data processing, we identified a total of 938 OTUs among all samples, which corresponded to approximately 200 unique OTUs shared between samples of each chip after filtering and removing singletons, which is similar to the scale of OTUs previously observed in human ileal aspirates (280 OTUs) 33 . Analysis of the alpha diversity between the two conditions showed that the species diversity in anaerobic chips were statistically different (PERMANOVA, p < 0.001) from aerobic chips ( Fig.…”
Section: Co-culture Of Human Intestinal Epithelium With An Obligate Asupporting
confidence: 55%
“…The epithelial channel of the chips was flushed daily with a short (2 min) fluid pulse at higher flow rate (50 l.min -1 ) to remove adherent and luminal bacteria, and 16S rRNA sequencing was carried out using samples from the effluent to assess bacterial diversity in each condition over 3 days of culture (n = 4 for each condition). 11 After data processing, we identified a total of 938 OTUs among all samples, which corresponded to approximately 200 unique OTUs shared between samples of each chip after filtering and removing singletons, which is similar to the scale of OTUs previously observed in human ileal aspirates (280 OTUs) 33 . Analysis of the alpha diversity between the two conditions showed that the species diversity in anaerobic chips were statistically different (PERMANOVA, p < 0.001) from aerobic chips ( Fig.…”
Section: Co-culture Of Human Intestinal Epithelium With An Obligate Asupporting
confidence: 55%
“…Rothia consist of aerobic and facultative anaerobic species. They are abundant in the distal ileum and also present in the oral microbiota (Segata et al, 2012;Villmones et al, 2018). Increased gastric pH and oxygen concentration in the distal GI might increase the abundance of this genus in the fecal microbiota following RYGB.…”
Section: Serum Bile Acidsmentioning
confidence: 99%
“…This and other studies have shown that the jejunal and proximal ileal microbiota are distinct from the colonic microbiota. 10,49 Despite changes in overall community structure and an overall decrease in microbial diversity across the stomach and small intestine compared stool, many of the same organisms commonly observed in stool were also present in the upper GI tract, albeit at very different abundances. 10 Interestingly, colonic resection and ileal pouch-anal anastomosis has been shown to shift the terminal ileum microbiota to a state similar to the colon, suggesting that a colonic community structure can develop at these sites given the right conditions.…”
Section: Discussionmentioning
confidence: 99%
“…10 Interestingly, colonic resection and ileal pouch-anal anastomosis has been shown to shift the terminal ileum microbiota to a state similar to the colon, suggesting that a colonic community structure can develop at these sites given the right conditions. 21,43,49-51…”
Section: Discussionmentioning
confidence: 99%